Homeopathic Posology - Swain, Trupti Laxmi (Homœopathic Links, 2013)
The subject of the dose is an integral part of homeopathy. The three essential elements of the system are the principle, the remedy and the dose. Posology is one of the cardinal principles. The article discusses various aspects of homeopathic posology – viz. its types, indication, administration – and distinguishes it from regular medicine. In addition, vital factors such as potency selection, dose repetition and duration are discussed.
Keywords: Posology; Potency; Dose; Repetition of dose